2022
DOI: 10.1021/acsenvironau.1c00056
|View full text |Cite
|
Sign up to set email alerts
|

pH-Dependent Partitioning of Ionizable Organic Chemicals between the Silicone Polymer Polydimethylsiloxane (PDMS) and Water

Abstract: The silicone polymer polydimethysiloxane (PDMS) is a popular passive sampler for in situ and ex situ sampling of hydrophobic organic chemicals. Despite its limited sorptive capacity for polar and ionizable organic chemicals (IOC), IOCs have been found in PDMS when extracting sediment and suspended particulate matter. The pH-dependent partitioning of 190 organics and IOCs covering a range of octanol−water partition constants log K ow from −0.3 to 7.7 was evaluated with a 10-day shaking method using mixtures com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 70 publications
(132 reference statements)
0
17
0
Order By: Relevance
“…Additionally, in environmental chemistry research, passive equilibrium sampling of dissolved contaminants in water has been studied using polymer polydimethylsiloxane (PDMS) as an absorbent phase. This hydrophobic passive sampler can extract ionizable compounds from sediments and suspended particulate matter in a pH‐dependent manner [101] . The authors tested the partitioning of ionizable compounds between PDMS and water (log D PDMS/w ) at different pH values.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, in environmental chemistry research, passive equilibrium sampling of dissolved contaminants in water has been studied using polymer polydimethylsiloxane (PDMS) as an absorbent phase. This hydrophobic passive sampler can extract ionizable compounds from sediments and suspended particulate matter in a pH‐dependent manner [101] . The authors tested the partitioning of ionizable compounds between PDMS and water (log D PDMS/w ) at different pH values.…”
Section: Resultsmentioning
confidence: 99%
“…This application demonstrated that the thermodynamic equilibrium derived in Equation 2 applies to partitions other than the n ‐octanol/water system, such as in the PDMS/water phases. The presence of some free silanol groups, combined with the highly hydrophobic polymeric chain might create a suitable environment for ionized‐organic species in the PDMS phase through a combination of hydrogen bonds from the terminal −OH groups and dispersion non‐covalent forces from the polymeric chains [101,134] …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This contradiction to common perception for the partitioning of IOCs has also been reported recently. For example, Niu et al 51 examined the pH-dependent partitioning behaviors of IOCs between water and polydimethylsiloxane polymer and found partitioning of the charged species of IOCs was smaller than their neutral and zwitterionic forms, but this difference was not negligible.…”
Section: ■ Results and Discussionmentioning
confidence: 99%